Macapat Ambiya as a Medium for Educating Islamic Values during the Neonatal Period - Rosy Tristanti; Aris Setiawan; Suyoto (Exploration in Early Childhood Research, 2024)
Macapat Ambiya is a traditional art form that continues to exist to this day. This art thrives and develops in the village of Kemloko, Nglegok subdistrict, Blitar regency. Macapat Ambiya is regularly performed during the birth of a baby and is held for seven consecutive nights. Macapat Ambiya, derived from the Serat An Nabiya, which contains many Islamic values, is sung by a group of men who visit the house of the newborn. The purpose of this performance is to introduce Islamic values to the baby. It is hoped that the Islamic education given from the first day of the baby's life will create a strong and lasting foundation for the newborn. The gentle and soothing chants of macapat are also expected to help the mother and baby feel calm and relaxed. The problem addressed in this research is: What is the role of Macapat Ambiya as a medium for instilling Islamic values during the neonatal period? This study aims to analyze the role of Macapat Ambiya as a medium for instilling Islamic values in newborns, which will be explored through the text of the macapat derived from Serat An Nabiya, which contains many Islamic stories about the prophets. This research uses a qualitative descriptive approach, focusing on the lyrics of the macapat ambiya songs that reference Islamic education for newborns. The results of this study show that the lyrics of the macapat ambiya songs, sourced from Serat An Nabiya by Yasadipura I especially in Pupuh Asmaradana contain many Islamic values that can be used as a medium for instilling Islamic values in newborns during the neonatal period.